The Fiscal Illusion: A Regional Paradox of Mining Resources (Study on Regencies/Cities in North Maluku) - Reza, Muhammad Dwi; Fahri, Johan; Amiro, Suratno; Ahmad, Abdul Chalid (AIBPM Publisher, 2024)
This study aims to determine the fiscal illusion of the mining area paradox in North Maluku Regency/City which is affected by the flypaper effect by regression on Regional Original Revenue, General Allocation Fund and Revenue Sharing Fund on Regional Expenditure. The data collection method uses census techniques. There are 10 districts/cities in this study with a total of 50 observations from 2018-2022. The technique used in this study is a multiple linear regression analysis technique using the E-Views 12 statistical test tool. The results of this study Fiscal illusions in North Maluku can include a variety of aspects related to perceptions or beliefs that may not correspond to the actual economic reality. Revenue from the mining sector, dependence on central transfer funds, increased revenue from massive investment are gaps in the occurrence of fiscal illusions in districts/cities in North Maluku Province. Regional Original Revenue, General Allocation Fund and Profit Sharing Fund affect regional expenditure and there is a flypaper effect symptom in districts/cities in North Maluku province.